The design of protozoan phosphoribosyltransferase inhibitors containing non-charged phosphate mimic residues. (15th November 2022) - Gai, Sinan; Suthagar, Kajitha; Shaffer, Karl J.; Jiao, Wanting; Minnow, Yacoba V.T.; Glockzin, Kayla; Maatouk, Sean W.; Katzfuss, Ardala; Meek, Thomas D.; Schramm, Vern L.; Tyler, Peter C.
Graphical abstract: Abstract: Phosphate groups play essential roles in biological processes, including retention inside biological membranes. Phosphodiesters link nucleic acids, and the reversible transfer of phosphate groups is essential in energy metabolism and cell-signalling processes. Phosphorylated metabolic intermediates are known targets for metabolic and disease-related disorders, and the enzymes involved in these pathways recognize phosphate groups in their catalytic sites. Therapeutics that target these enzymes can require charged (ionic) entities to capture the binding energy of ionic substrates. Such compounds are not cell-permeable and require pro-drug strategies for efficacy as therapeutics. Protozoan parasites such as Plasmodium and Trypanosoma spp. are unable to synthesise purines de novo and rely on the salvage of purines from the host cell to synthesise free purine bases. Purine phosphoribosyltransfereases (PPRTases) play a crucial role for purine salvage and are potential target for drug development. Here we present attempts to design inhibitors of PPRTases that are non-ionic and show affinity for the nucleotide 5′-phosphate binding site. Inhibitor design was based on known potent ionic inhibitors, reported phosphate mimics and computational modelling studies.